Transformational leadership - Palanithurai, G. (South Asian Journal of Socio-Political Studies)
Today the world is so integrated so closely due to the technological innovations and people are connected for local and global actions. The communication revolution that broke out in the world intensified human activities to reach material advancement beyond human imagination. The communication revolution has changed the development landscape in an unexpected direction which resulted in competition and conflict between and among individuals, groups, communities, societies, countries, companies, organizations, and institutions. When the technological revolution was on, it was predicted that these changes would bring people together to lead harmonious and happy civilized life by integrating themselves with other communities, groups, and societies, and thereby a new global social order would emerge.- Reproduced